1978-1979ネン マクマード チイキ コクサイ キョウドウ カンソク ホウコク - 西尾, 文彦; ニシオ, フミヒコ; 白石, 和行; シライシ, カズユキ; 船木, 実; フナキ, ミノル; Nishio, Fumihiko; Shiraishi, Kazuyuki; Funaki, Minoru (1980)
P(論文) 1978-1979年の日米共同隕石探査は第3年目にあたる.今回は,マクマードサウンド地域以外で新たに隕石の発見の可能性が高いダーウィン氷河周辺での訓隕石探査が,主眼であった.その結果,11月14日から1月14日にかけてビクトリアランド・アランヒルズの裸氷上で,266個(このうち3個は不明),ダーウィン氷河源流域で12月3日から30日にかけて44個の鉄質隕石,石質隕石を発見し,合計310個,総重量400kgの隕石を発見回収した.アランヒルズの裸氷域では隕石集積機構に関連した氷河調査が実施され,三角鎖の設置・測量および年代測定などを行うための氷試料の採集が行われた.日本隊独自の活動としてドライバレー地域での地質調査および古地磁気学的研究のための試料の採集が実施された. To carry out four research programs, three Japanese scientists visited McMurdo Station and Victoria Land for a period from October 27, 1978 to January 19, 1979. Search for Antarctic meteorites : A U. S. -Japan meteorites search project was continued in the 1978-79 season in Victoria Land. Four U. S. participants and three Japanese revisited the bare ice field in the Allan Hills in Victoria Land, 230km north of McMurdo Station. Newly selected searching sites for this season are located in the blue ice field around the Darwin Glacier, namely, Boomerang Range, Warren Range, Finger Ridges, Butcher Ridge, Upper Darwin Glacier, Darwin Mountains, Turnstile Ridge, Westhaven Nunatak, Bates Nunataks and Lonewolf Nunataks. During this season, a total of 310 individual specimens were collected. Glaciological survey in the Allan Hills bare ice field : To clarify the accumulation mechanism of many meteorites on the bare ice surface of a limited small area near the Allan Hills, a triangulation line about 15 km long was installed in the bare ice field on the plateau side of the Allan Hills during the period from December 7, 1978 to January 2, 1979. Ice samples for the dating and crystallography were collected from this bare ice field. Geological survey in the Dry Valley area : Survey of the basement metamorphic rocks was conducted in the Dry Valley and Miers Valley area. Many dikes and their mutual relationship near Vanda Station of the Wright Valley were surveyed. The succession of intrusion is as follows in order of time : Black-colored lamprophyre A and B, grey-colored lamprophyre, porphyry A, B, and C, granite porphyry A and B, felsitic dike, basalt (Ferrer dolerite) and acidic dike ...